Genere letterario e performatività: una prospettiva teorica (Comparatismi, 2025)
Building on the concept of performativity as developed by J. L. Austin and the critical and social reinterpretation of this concept by Judith Butler, gender can be viewed as a construct formed and reinforced through the act of expression. Based on this idea, this article analyses performativity as a useful interpretative tool for understanding literary genre dynamics, challenging essentialist ideas to emphasise the pragmatic-relational dimension of genre. To illustrate this, two recent literary phenomena will be considered: the New Weird and climate fiction.
Keywords: Performativity; Literary Genre; Butler; Austin